The association between high blood pressure, physical fitness and fatness in adolescents - Gontarev Seryozha; Kalac, Ruzdija; Zivkovic, Vujica; Velickovska, Lence A; Telai, Besnik (ARAN Ediciones, 2017)
ntroduction: Hypertension is a health problem that is of national importance. It is a major risk factor for the occurrence of atherosclerosis and cardiovascular, cerebrovascular and renal diseases that are leading or among the leading causes of mortality and morbidity as in ours, as in the most developed and less developed countries. Objective: The purpose of this study is to analyze the relation of cardiorespiratory fitness and obesity, blood pressure and hypertension for adolescents. Material and methods: The research was realized on a sample of 4,051 boys and girls at the age of 11 to 14 years. Cardiorespiratory fitness was assessed by using a three minute step test, while the percentage of body fat was determined by bioelectrical impedance method. Blood pressure was measured three times at intervals of 60 seconds, and the result was the median value of the three measurements. The measurements were performed in a separate room with optimum ambient conditions. The relation between hypertension, cardiorespiratory fitness and fat was determined by correlation and multi-nominal logistic regressive analysis. Results: Boys had higher systolic pressure and lower diastolic pressure compared to girls. The low level of cardiorespiratory fitness and high percentage of body fat were independently associated with an increased risk of blood pressure and hypertension for both boys and girls. The interaction was established between the percentage of body fat and fitness. Conclusion: The results should be taken into account for building strategies and recommendations for improvement of lifestyle and health for adolescents.
Keywords: Blood pressure. Physical fi tness. Fatness. Adolescent.